Tele-Herbal Medicine di Klinik Kesehatan: Tinjauan Sistematis Implementasi, Efektivitas, dan Tantangan dalam Layanan Kesehatan Terpadu - Kartika, Ronald Winardi; Djuartina, Tena (Lembaga Pengembangan Kinerja Dosen, 2025)
Tele-Herbal Medicine is a technology-driven service designed to deliver herbal medicine consultations and therapies through wellness clinics, aiming to improve access to personalized and affordable care. This study systematically assesses its effectiveness, implementation, and challenges as part of integrated health services by reviewing relevant literature published in the past five years. Findings indicate that Tele-Herbal Medicine significantly enhances patient access, offering tailored and cost-efficient herbal treatments. Despite these promising outcomes, implementation faces key obstacles, including inadequate regulatory frameworks, the absence of standardized herbal product validation procedures, and concerns over patient data security. These limitations underscore the urgent need for comprehensive policies, quality assurance mechanisms, and strict data protection protocols, consistent with broader telemedicine guidelines. By addressing these issues, Tele-Herbal Medicine can evolve into a reliable and sustainable model, enabling wellness clinics to expand services without compromising safety or quality. Ultimately, its success depends on clear legal support, standardized validation systems, and robust monitoring tools to ensure effectiveness, safety, and full integration into the healthcare ecosystem, thus positioning it as an innovative solution that bridges traditional herbal practices with modern digital health services.